ELIMINATING ENFORCED IDLENESS OF RESOURCES AND JOB WAITING TIME IN TIME CONSTRAINED CONSTRUCTION ACTIVITIES USING WAITING LINE THEORY - Oluseye OLUGBOYEGA (Journal of Construction Project Management and Innovation)
Waiting of labour on construction site is a waste of energy and has been described as a shortcoming and production waste that can affect work performance and profitability of contractors. Labours are expected to be flowing through the construction site and not to be stationary; but when activities are not well designed, their capacities are withheld and are forced to be idle. Also, conventional job design techniques focus on planning of operations and required operatives without considering the elimination of waste related to operatives. Hence, this study explored the application of waiting line theory to eliminating the cost of waiting time of resources using the construction of a hypothetical upper floor slab. The practical application of waiting line theo ry was demonstrated and conclusions were drawn from the findings of the study. The findings revealed that waiting line theory can be applied in the design of time constrained construction activities so as to eliminate enforced idleness on construction sites through reduction in the waiting time of resources.